Synthesis, Molecular Docking and ADME-TOX Studies of New Tacrine Analogs as Promising for Alzheimer's Disease Therapy - Baba-Ahmed, Ikram; Kibou, Zahira; Daoud, Ismail; Belhadj, Fatima; Lahcen, Belarbi; Daich, Adam; Choukchou-Braham, Noureddine (Current Organic Chemistry, 2022)
The modification of drug delivery routes can be used as a promising strategy to improve the therapeutic profile of various drug agents. Herein, the synthesis and molecular modeling of a series of 6,7,8,9-tetrahydrobenzo [b] [1,8] naphthyridines derivatives were reported to explore potent and less toxic scaffolds. The tacrine analogs 6-10 were obtained by an efficient strategy using Friedlander's condensation between 2-aminopyridine-3-carbonitriles 1- 5 and cyclohexanone under microwave irradiations without catalysts and solvents. The synthesized compounds were identified through 1H NMR, 13C NMR, IR. Their inhibition activities against acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) were focused as probable drug targets for Alzheimer’s disease (AD). The pharmaco-kinetic properties, the risk of probable hepato-toxic metabolites, and the toxicological properties were predicted using computational methods. The prediction of the toxicity risks via the GUSAR software allowed us to resolve the best approach for drug delivery, namely the subcutaneous, intravenous, or oral route., Also, the GUSAR software was used to reveal all possible adverse effects. All these techniques were tested for the L1-6 compounds by choosing tacrine as a template compound. Among these compounds, the optimal compound L1 was the most potent inhibitor and had the best score binding affinity compared to the reference drug (Tacrine) -7.926 and -7.007 kcal/mol for AChE and BuChE, respectively. Moreover, this same compound presented a satisfying pharmaceutical profile. In the present study, subcutaneous delivery is considered a promising administration of reference drug and their derivatives against AD.
Keywords: Alzheimer’s disease